Recommendations for follow-up of muscle-invasive bladder cancer patients: A consensus by the international bladder cancer network - Zuiverloon, TCM; van Kessel, KEM; Bivalacqua, TJ; Boormans, JL; Ecke, TH; Grivas, PD; Kiltie, AE; Liedberg, F; Necchi, A; van Rhijn, BW; Roghmann, F; Sanchez-Carbayo, M; et al. (Elsevier, 2018)
Several guidelines exist that address treatment of patients with nonmetastatic muscle-invasive bladder cancer (MIBC). However, most only briefly mention follow-up strategies for patients and hence the treating physician is often left to infer on what the preferred follow-up schema would be for an individual patient. Herein, we aim to synthesize recommendations for follow-up of patients with MIBC for easy reference.A multidisciplinary MIBC expert panel from the International Bladder Cancer Network was assembled to critically assess currently available major guidelines on surveillance of MIBC patients. Recommendations for follow-up were extracted and critically evaluated. Important considerations for guideline assessment included both aspects of oncological and functional follow-up-frequency of visits, the use of different imaging modalities, the role of cytology and molecular markers, and the duration of follow-up.An International Bladder Cancer Network expert consensus recommendation was constructed for the follow-up of patients with MIBC based on the currently available evidence-based data.